Hospital Wastewater Pharmaceutical Residues and Their Impact on Community Microbial Resistance: An Epidemiological and Pharmaceutical Systematic Review - Giyantolin Giyantolin; Yuli Subiakto; Timbul Partogi Haposan Simorangkir; Widyati Widyati (Indonesian Journal of Global Health Research, 2025)
Releases from healthcare facilities account for a large portion of environmental pollution, with wastewater carrying a cocktail of pharmaceutical contaminants, especially antibiotics. These compounds accelerate the accumulation of antimicrobial resistance. Objective: The study synthesizes the scientific record on the concentration, fate, and effects of pharmaceutical compounds within hospital wastewater; it foregrounds the links to growing microbial resistance and delineates the threat to public health. The review adhered to the 2020 PRISMA framework. The search strategy applied a combination of keywords ("pharmaceutical residues" OR "antibiotic residues") AND ("hospital wastewater") AND ("antimicrobial resistance") AND ("environmental impact" OR "community"). The search was restricted to titles and abstracts of studies published 2015-2025. The article selection process consisted of title and abstract screening, full-text evaluation, and consensus-based discussion. Of the 405 articles initially identified, 21 met the eligibility criteria and were narratively synthesized. Hospital wastewater was found to contain a variety of antibiotics, particularly β-lactams, fluoroquinolones, tetracyclines, macrolides, and sulfonamides, at concentrations higher than those observed in domestic wastewater. Several ARGs including blaNDM, blaKPC, blaOXA, sul1, sul2, qnr, tet, and mcr were frequently detected, alongside resistant pathogenic isolates such as Escherichia coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa. Conventional wastewater treatment processes were shown to be only partially effective, achieving removal efficiencies of 16-50% for pharmaceutical residues and ARGs. Consequently, resistant bacteria and ARGs were still detected in receiving water bodies several kilometers downstream from discharge points. Hospital wastewater serves as a major source of pharmaceutical contamination and plays a critical role in the amplification of microbial resistance in the environment. These findings highlight the urgent need for advanced wastewater treatment technologies, strengthened antibiotic stewardship programs, and the integration of environmental and epidemiological surveillance within the One Health framework to curb the spread of antimicrobial resistance.